2019
DOI: 10.1088/1361-6463/aafaa9
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the electronic and spintronic properties of monolayer GaGeTe with a vertical electric field

Abstract: Development of two-dimensional (2D) nanoelectronics is appealing for electrically tunable properties in 2D materials. By means of density functional theory computations, we systematically study the modulation of vertical electric field on the electronic structure and spintronic properties of monolayer GaGeTe. A transition from indirect to direct bandgap is realized with an electric field of 0.11 V Å −1 . The direct bandgap monotonously diminishes due to the giant Stark effect with a Stark coefficient of 3.68 Å… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
(40 reference statements)
0
8
0
1
Order By: Relevance
“…The application of an external electric field is widely used not only in theory but also in experiments to tune the electronic structure of 2D materials. The effect of the external electric field on the electronic properties of the ZrS 2 /MoTe 2 heterostructure was investigated. Here, the direction of the positive electric field is designated as pointing from the ZrS 2 layer to the MoTe 2 layer.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The application of an external electric field is widely used not only in theory but also in experiments to tune the electronic structure of 2D materials. The effect of the external electric field on the electronic properties of the ZrS 2 /MoTe 2 heterostructure was investigated. Here, the direction of the positive electric field is designated as pointing from the ZrS 2 layer to the MoTe 2 layer.…”
Section: Results and Discussionmentioning
confidence: 99%
“…26,49 The electric eld can be used to modulate the positions of VBM and CBM in 2D semiconductors, such as the CBM shis to low energy as an external electric eld applied perpendicular to the surface of GaGeTe monolayer. 50 The electric eld also can modify the band alignment of 2D heterostructures, 26,28 such as a type II band alignment transforms to type III one as an the electric eld is larger than 0.6 VÅ À1 in MoTe 2 /WSe 2 heterostructure. 51 The effects of external electric eld on the band alignment of MoS 2 /C 3 N heterostructure were investigated by decreases with the increase of negative electric eld and increases with the positive electric eld.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the charge redistribution in materials due to the applied external electric field can lead to changes in their electronic features. For example, previous studies indicated that the the band gaps of the group III monochalcogenides and their Janus structures depends strongly on the external electric fields [51][52][53]. Particularly, the transition from indirect to direct band gap is found in monolayer GaSe when the electric is applied [52].…”
Section: Electronic Propertiesmentioning
confidence: 99%